Keeping up with the e-Joneses: Do online social networks raise social comparisons? - Fabio Sabatini; Francesco Sarracino (Kiel Institute for the World Economy (IfW), 2018)
Online social networks, such as Facebook, amplify the occasions for social comparisons which are detrimental to well-being. The authors test the hypothesis that the use of social networking sites (SNS) increases social comparisons using Italian data from the Multipurpose Household Survey, and European data from Eurobarometer. The results suggest that SNS users have a higher probability to compare their achievements with those of others. This evidence is robust to endogeneity concerns. The authors conclude that, by increasing the opportunities for social comparisons, SNS can be an engine of income dissatisfaction for their users.
Keywords: D83; I31; O33; Z1; Z13; 330; social networks; social networking sites; social comparisons; satisfaction with income; relative deprivation